Jasmonoyl-l-isoleucine and allene oxide cyclase-derived jasmonates differently regulate gibberellin metabolism in herbivory-induced inhibition of plant growth. (November 2020) - Yang, Fei; Tang, Jinxiang; Yang, Dahai; Yang, Tianyu; Liu, Hui; Luo, Wanni; Wu, Jinsong; Jianqiang, Wu; Wang, Lei
Highlights: Herbivory-induced stunted growth is partially dependent on JA-Ile. Herbivory-induced growth retardation is caused by GA4 deficiency. Herbivory suppresses GA biosynthetic genes, but activates GA catabolic genes. JA-Ile only regulates the transcriptions of certain GA catabolic genes. Jasmonates other than JA-Ile also regulates GA metabolism-related genes. Abstract: The trade-off between plant growth and resistance to herbivory is thought to be at least partly mediated by the interactions between jasmonates and gibberellins (GAs). Insect herbivory activates jasmonate biosynthesis and signaling, and plant growth is concomitantly inhibited. Whether or not the herbivory-induced jasmonates suppress the accumulation of GAs and thus reduce plant growth, and which jasmonates are functional in this process, remain unclear. In this study, we show that herbivory-induced stunted growth of Nicotiana attenuata was completely dependent on allene oxide cyclase ( AOC ) and coronatine insensitive1 ( COI1 ), which encode a JA biosynthetic enzyme and the receptor, respectively, but only partially dependent on jasmonic acid-isoleucine conjugate (JA-Ile), the bioactive jasmonate. Quantification of GAs and exogenous treatments indicated that herbivory-induced growth inhibition was caused by GA4 deficiency, and that the reduction in GA4 accumulation was strongly associated with both decreased concentrations of GA biosynthetic gene transcripts and transcriptional activation of GA catabolic genes. We further show that JA-Ile only positively regulated the levels of GA catabolic genes, while the accumulation of GA biosynthetic gene transcripts was controlled by certain AOC-derived jasmonate(s) rather than by JA-Ile. This work sheds light on the mechanisms by which plants adapt to herbivory by using intricate phytohormone signaling and transcriptional regulatory networks.